The effects of a combined multi-stressor environment and fatigue on pistol shooting performance - Salmon, O. F. (The University of Texas at El Paso, 2021)
Occupationally relevant skills including pistol or rifle marksmanship among service members require a combination of cognitive, visual, and neuromuscular coordination (Rifle & Carbine, 2019). Accuracy is anessential parameter of marksmanship and is defined as the distance from the desired point of impact of the projectile and the actual point of impact on the target (Rifle & Carbine, 2019). Training to become a proficient marksman takes several weeks, accruing numerous hours of classroom and field training. Upon successful completion of marksmanship training, service members will have the necessary skills to properly operate and fire small arms weaponry (Grandizio et al., 2014). Recently, the U.S. Army indicated the need to improve the adaptability of weapon training strategies to meet current and future operational environments (Crowley et al., 2014). The improvement of small arms qualification training by simulating acute environmental changes experienced in austere environments, including heat, cold, and altitude, have been linked to greater success inmany past military operations (Rodway & Muza., 2011). Until recently, live-fire training has been the only approved method for small arms field training and marksmanship skill development (Dyer et al., 2010). However, in the latest revision of the U.S. Army`s Training and Qualification-Individual Weapons manualreleased in 2019, electronic weapon simulators are an approved method for use during marksmanship training (Training and Qualification -Individual Weapons, 2019). Training simulators can improve marksmanship performance by providing additional feedback and performance metrics while also increasing the number of practice sessions compared to live fire practice (Mitchell & Brossi, 2016). In addition to improved training efficiency and cost benefits of an electronic-based marksmanship simulator, the practicality, portability, and safety of electronic weapon simulatorscan providea cost-effective method for testing marksmanship performance within a combination of environments, such as simulated normobaric hypoxia, or various thermal environments within a temperature-controlled room.